(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to determine students’ mathematical communication skills after the application of the problem based learning model of number pattern material in grade VIII students of SMP Negeri 4 Loura. The type of research is a descriptive qualitative method. Data collection uses interviews and documentation. The data analysis process is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawn. The results of the study showed that from each level of the percentage level of the student communication ability category, namely the percentage level of the high category was 20%, medium 20% and low 60%. The impact of this ability is that students do not relearn the material that has been given during learning and do not pay attention to the researcher delivering the material